Pengaruh Kualitas Produk, Value For Money dan Kualitas Pelayanan terhadap Keputusan Menginap di The Patra Bali Resort & Villas - I Gusti Ayu Aurilia Dewi Sekarini; Ni Nyoman Teristiyani Winaya; I Gusti Ketut Gede (Lembaga Pengembangan Kinerja Dosen, 2026)
The increasing competition in the hospitality industry requires hotels to continuously improve product quality, deliver excellent service, and provide value that matches the price paid by customers. These factors play an important role in influencing guests' decisions when choosing accommodation. This study aims to analyze the influence of product quality, value for money, and service quality on guests' stay decisions at The Patra Bali Resort & Villas. This research employs a quantitative approach, with data collected through questionnaires distributed to guests who have stayed at The Patra Bali Resort & Villas. The collected data will be analyzed to examine the relationships among the research variables. The findings are expected to contribute to the development of marketing management knowledge in the hospitality industry and provide useful insights for hotel management in improving guests' stay decisions.